2008
DOI: 10.1002/jbm.a.31604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of passivation treatments on titanium alloy with nanometric scale roughness and induced changes in fibroblast initial adhesion evaluated by a cytodetacher

Abstract: Passivation treatments of titanium alloy alter not only its nanosurface characteristics of oxides and ion release but also surface roughness (Ra), and wettability as well, where nanosurface characteristics of oxides include chemistries of oxides, amphoteric-OH groups adsorbed on oxides, and oxide thickness. Consequently, the passivation treatment affects the alloy's cyto-comparability. In this study, we polish specimens to achieve nanometric scale roughness. In addition, treatment effects are evaluated for sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 28 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…In the field of biomaterial researches, the cellbiomaterial interaction can be modulated by the surface characteristics of the material. Recently, it has been reported that an improvement in surface wettability of biomaterials can promote cell survival and attachment (Sawase et al 2008, Machida-Sano et al 2009, Wang et al 2009, Ke et al 2010. In the broadest sense, dentine is a special type of biomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of biomaterial researches, the cellbiomaterial interaction can be modulated by the surface characteristics of the material. Recently, it has been reported that an improvement in surface wettability of biomaterials can promote cell survival and attachment (Sawase et al 2008, Machida-Sano et al 2009, Wang et al 2009, Ke et al 2010. In the broadest sense, dentine is a special type of biomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…While there are many ways to generate irregular nanoscale features such as roughness [33][34][35], there are only a few methods for generating highly defined nanostructures. Most of the techniques are based on some form of lithography [36], soft lithography [37][38][39], e-beam etching [40,41], dip-pen [42,43], or conventional lithography [44,45].…”
Section: Nanostructured Biomaterialsmentioning
confidence: 99%
“…Conversely, the application of CaP on nanotube arrays altered the wettability from hydrophilic to hydrophobic. The initial morphology of cells on biomaterials can be used as an indicator of cyto-compatibility [30]. Cell attachment to the surface of specimens was observed using SEM.…”
Section: Biocompatibilitymentioning
confidence: 99%